Development of monoclonal antibodies against porcine blood for detection in fish-based products - Raja Nhari, Raja Mohd Hafidz (2017)
Animal blood mainly from porcine and bovine have been used in human food as a binder, gelling agent, emulsifier, coloring agent and iron’s supplementary in most meat and fish-based products. However, certain communities including Muslims and Jews are strictly prohibited to consume animal blood in food due to prohibition assigned by each religious and related to health and personal matter. The addition of porcine plasma in fish surimi has been highlighted by the local authority in Malaysia. To date, a specific method to detect porcine plasma in food is unavailable. In this study, we have developed monoclonal antibodies (mAbs) against heated soluble proteins (HSPs) of porcine blood using fusion technology for detection of porcine plasma in fish surimi. Specificity of mAbs against blood, non-blood (meat and nonmeat) and commercial animal plasma proteins from different species were determined using indirect non-competitive ELISA. Antigenic components of porcine blood were determined using Western blot. The sensitivity of ELISA has been determined to analyze fish surimi that spiked with porcine plasma. After several screening of hybridoma was made, 27 hybridomas produced mAbs were selected. Based on that, fifteen mAbs are specific to raw and heated porcine blood, one mAb only specific to raw porcine blood and another 11 mAbs are cross-reacted with other animal blood. The fifteen mAbs specific to porcine blood are also not cross-reacted with meat and non-meat proteins. Based on specificity to animal plasma, twelve mAbs from 15 mAbs are specific to porcine plasma while other 3 mAbs are cross-reacted to chicken plasma. Western blot showed that 2 mAbs bind 60 kDa, 8 mAbs bind 85 kDa and 2 mAbs bind 250 kDa of the antigenic protein of porcine blood. The mAb labeled as B4E1 was selected to be used for detection of porcine plasma. The developed ELISA has a limit of detection (LOD) and limit of quantification (LOQ) of 0.2 μg/g and 1 μg/g, respectively for a standard solution of porcine plasma. The intra- and inter-assays of ELISA with coefficients of variation (CVs) less than 20% were able to detect at least 0.25% (w/w) porcine plasma in fish surimi. In conclusion, this study has successfully obtained the hybridoma-producing mAbs that are specific to porcine blood and porcine plasma. This study also has developed indirect non-competitive ELISA for detection of porcine plasma in laboratory model fish ball and fish surimi products using mAb B4E1 with LOD and LOQ of 0.2 μg/g and 1 μg/g, respectively with the sensitivity of the ELISA is 0.25% (w/w) porcine plasma in fish surimi.